A Single Center, Prospective, Randomized, Sham-Controlled, Double-Blinded, Split-Face Trial Using Microinjections of Transparent Hyaluronic Acid Gel for Cheek Rejuvenation. Issue 6 (June 2018) - Jones, Isabela T.; Vanaman Wilson, Monique J.; Bolton, Joanna; Zaleski-Larsen, Lisa; Wu, Douglas C.; Goldman, Mitchel P.
Abstract : BACKGROUND: "Skin boosting" with injections of hyaluronic acid has been demonstrated to improve aged skin. OBJECTIVE: The aim of this study was to determine the efficacy and safety of small-particle hyaluronic acid with lidocaine (SP-HAL) microaliquots for the correction of fine lines of the cheeks. MATERIALS AND METHODS: Twenty subjects with mild to moderate static mid to lower cheek rhytides were enrolled. The right or left cheek was randomized to receive 1 mL of SP-HAL using a microdroplet technique, with the contralateral cheek treated with sham injection of sterile normal saline. The degree of cheek wrinkling and elastosis based on the Fitzpatrick-Goldman Wrinkle and Elastosis Scale was assessed at baseline and 7, 14, 30, 90, and 180 days after treatment. Subjects rated their satisfaction at days 90 and 180. RESULTS: Fourteen patients completed the study. There were no statistically significant improvements in wrinkling or elastosis of the SP-HAL–treated cheek or control cheek at any time point. In addition, there were no significant differences in wrinkling, elastosis, or patient satisfaction between the treatment cheek and control cheek. CONCLUSION: One treatment of intradermal microdroplet injections of SP-HAL to the mid to lower cheek failed to show superiority over normal saline in improving clinical signs of skin wrinkling and elastosis.